Tasks of the hospital emergency department during disasters - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Robert Czerski; Dorota Lasota (Kazimierz Wielki University, 2018)
Hospital emergency departments with emergency medical teams are the basic units of the National Medical Rescue System. Hospital emergency department is an independent organizational unit within the meaning of the hospital health care facilities, providing the benefits of health care that persons in a state of sudden health threat, satisfying the Requirements of the Act of 8 September 2006 about the National Medical Rescue System. In research presents the procedure of dealing in the situation of a disaster of the hospital emergency department. Characterized in details the mobilization personnel system, the role of hospital emergency staff and hospital staff jobs in emergency department in the situation of disaster.